SYMBOLIC ANALYSIS OF CHINESE IDENTITY RECOGNITION IN THE UGLY VEGETABLES PICTURE BOOK BY GRACE LIN (1999) - Putra, Rhema Krispatria (Universitas 17 Agustus 1945 Semarang, 2024)
Identity, Symbol, Picturebook